Digitalisasi Pengelolaan Dana Desa di Desa Bina Baru Kabupaten Sidenreng Rappang - Razak, Muhammad Rais Rahmat; Nonci, Nurjannah; Lubis, Sandi; Dayadi,; Khaerunnisa, Mutiah (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study analyzes the digitization of village fund management in Bina Baru Village, focusing on implementation conditions, stakeholder roles, and strategies for improving effectiveness. Using a qualitative approach with NVivo 12 Plus data analysis through in-depth interviews with Village Head, Finance Head, Village Operator, Village Secretary, and Community Leaders. The research results show that digitization of village fund management experiences paradoxical conditions with partial achievements in various aspects. Digital systems have been successfully implemented operationally internally and provide convenience for village officials in administrative and managerial functions. However, digitization faces significant challenges in public accessibility aspects where the community cannot access digital systems, so the principles of transparency and public accountability have not been optimally achieved. Digital transformation involves collaborative roles from various stakeholders with clear differentiation. Strategies to improve digitization effectiveness require a comprehensive approach including increasing accessibility through public digital portals, stabilizing technical infrastructure, developing human resource capacity, increasing community participation with digital consultation mechanisms, and multi-stakeholder collaboration.